Laser curve scanning forming process of laminated metal composite plate. (June 2020) - Wang, Xiaogang; Shi, Yongjun; Guo, Yankuo; Sun, Rui; Li, Xianfa; Zhou, Xiaoyu
Abstract: To analyze the deformational behaviors of laminated metal composite plate under laser curve scanning, a numerical 3D nonlinear thermodynamic coupling model was constructed for a three-layer stainless steel composite plate, 06Cr19Ni10/1Cr17Mn6Ni5N/06Cr19Ni10. The effects of curvature M of the scanning path, laser power P, scanning velocity V, and the distance H e from the scanning line to the free end on the forming process were investigated. The numerical model and research contents were experimentally verified. Results showed that the plate under laser curve scanning underwent double-curvature deformation. The deformational curvature of the free end of the plate increased with the curvature of the scanning curve. Plate forming accuracy could be improved by reasonably controlling laser power and scanning velocity. The bending angle of the plate was approximately in direct proportion to H e . The crystal grains of the formed plate under optimized process parameters were refined without lamination phenomenon. Graphical abstract: Unlabelled Image Highlights: A numerical nonlinear thermodynamic coupling model was constructed for the three-layer stainless steel plate. The plate under laser curve scanning underwent double-curvature deformation. Laser power and scanning speed are critical to forming accuracy. The crystal grains of the formed plate under optimized process parameters were refined without lamination phenomenon.